Mapping the English Proficiency of Junior High School English Teachers Across Riau Province - Syarfi, Muhammad; Ras, Fakhri; Masyhur, Masyhur (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research aims at getting a solid map of standard English Proficiency possessed and used by Junior High School English teachers throughout Riau Province, which covers Listening, Structure, Vocabulary and Reading Comprehension. The indicators of the standard English Proficiency are scores (high, moderate, and low) obtained by English teachers in TOEFL test. The subjects of the research are all Junior High School English teachers throughout Riau Province (613 teachers), all of whom become the research samples. The research instrument is TOEFL Equivalent intended to get a solid map of standard English Proficiency of the teachers. Research data were comprehensively analyzed to describe the English Proficiency of the teachers based on seven factors; gender, employment status, level of education, University alma mater, length of teaching period, attended trainings, and ethnics. By and large, data analysis results in the followings: a) English Proficiency of male English teachers is better that that of female ones, each of whose average scores are 407,8 â 391,4, b) English Proficiency of Non Civil Servant teachers is a bit higher than that of those Civil Servant ones, each of whose average scores are 392,16 and 393,9, c) The higher the level of education of the teachers, the higher or the better their English Proficiency, d) English Proficiency of teachers graduated from State University is better than that of those from Private University, whose average scores are 399,1 and 378,6, e) English Proficiency of the teachers teaching between the periods 1 up to 10 years is the highest (average score 401.7), followed by the teachers whose teaching period is between 11 and 20 years, then 21 up to 30 years and the last or the worst are those whose teaching period is above or longer than 31 years, f) English Proficiency of the teachers who have ever attended training on English is better than that of those who have not, each of whose average scores are 396.3 and 380.9, g) English Proficiency of Javanese English teachers is the best among the other ethnics, whose average score is 421.7, and then Malay English teachers, whose average score is 392.6, and then followed by Batak English teachers whose average score is 369.6, and the last is the English teachers from Minang ethnic, whose average score is 329.8. It can be inferred that the English Proficiency of Junior High School English teachers throughout Riau Province is generally below the expected target for their average score is still less than 450.